Integration of Information System Based on Supply Chain Management (SCM) for Pharmaceutical Warehouse in Mamasa Regency - Qashlim, Akhmad; B, Basri (Bina Nusantara University, 2018)
This research applied information system by using Supply Chain Management (SCM) in the pharmaceutical warehouse in Mamasa Regency. The scope of the research was maximized on pharmaceutical warehouse operations and drug distribution to clinics. This research did not focus on cost, profit, lead time, and procurement costs. This system was built using PHP programming language and MySQL database. System development process used waterfall method. It consisted of requirement analysis, system analysis, design, development, and testing. The test system used the xampp 6.2 servers with a black box testing method that involved the pharmaceutical warehouse staff as the end user. The results demonstrate technologies that can be used by physicians to submit drug requests faster and report on real-time drug use (LPLPO). For pharmaceutical warehouses, this system is useful for drug availability, drug management, and response information. This technology can help the health department to perform its role as a supervisory or controlling function (internal controls) of the drugs. This research also gives a recommendation for the pharmaceutical warehouse management in providing benefits for the institutions/companies involved. This research has an insight for the management to realize the importance of Information Technology (IT) to support daily operational activities.